Natural Convection and Radiation in Enclosures with Semi-transparent Medium: Conjugate CFD Analysis - E. G. Barbosa; M. E. V. Araujo; M. A. Martins; E. G. Barbosa (Journal of Applied Fluid Mechanics, 2022)
Radiation heat transfer is often ignored in several studies as it has few significant effects in some cases. However, when using a participating fluid, where the molecules interact with the radiative spectrum, these effects cannot be disregarded. A numerical study of the heat transfer by natural convection and radiation in two square enclosures (with and without protrusions) using a transparent (non-participating) and semi-transparent (participating) fluid medium was carried out in this study. The governing equations were discretized using the finite volume technique and solved using a CFD code ANSYS CFX. The heat transfer by radiation was modeled using the differential approach. The model proposed in this study was validated with the data available in the literature with errors of less than 3%. The results showed that the addition of the participant fluid (CO2) promotes a better condition for heat transfer. It was proven that the use of the participating medium caused an increase in the Nusselt number, indicating an increase in heat transfer by convection. The presence of protrusions reduces the thermal stratification zone for the pure convection case (CP) and provides a better temperature distribution for the cases conjugated with air (CRAIR) and CO2 (CRCO2) when compared to the cases without protrusions. It is observed that for all cases, the geometry with protrusion presented the highest values for the Nusselt number, indicating that the insertion of the protrusion increases the heat transfer in the enclosure by up to 11%. The airflow values for the conjugated cases are more than 300% higher than those presented for the pure convection case for any Rayleigh number value. The heat flow increased by up to 4 times when the radiation effect was considered. The average Nusselt number increased with the increase in the Rayleigh number and with the coupling of radiation in the energy equation. This indicates that the effect of radiation cannot be disregarded in the study of heat transfer in enclosures.